Analyses of community stability and inter-specific associations between a plant species with extremely small populations (Hopea hainanensis) and its associated species - Zhang, Li; Zhang, Hai-Li; Chen, Yukai; Nizamani, Mir Muhammad; Zhou, Qin; Su, Xiting (Frontiers in Ecology and Evolution, 2022)
Hopea hainanensis is a large evergreen tree belonging to the family Dipterocarpaceae. It is currently listed as an endangered species on the International Union for Conservation of Nature's (IUCN) Red List of Threatened Species. It is found primarily on China's Hainan Island and northern Vietnam. To protect the endangered species Hopea hainanensis, understand its community stability and Interspecific associations. We set up 16 quadrats in the areas where wild slope barriers are distributed on Hainan Island to investigate the composition of plant species in the quadrats. Community stability was determined using the M. Godron Community stability method. Based on the two × two contingency tables, the statistic X2, association coefficient (AC) and Pearson correlation coefficient (PCC), percentage co-occurrence (PC), and OI index (OI) to analyze the degree of association between slope barriers and dominant species in each layer. The results showed that the relationship between the Hopea hainanensis and the dominant species in the community was not significant. In addition, there were positive and negative associations with six species of trees, positive associations with species of 13 shrubs, positive associations with two species of herbs, and negative associations with species of 7 species. The connection between the slope barrier population and herbs is more complex than between trees, shrubs, and the dominant species. Moreover, M.Godron stability analysis showed that the Hopea hainanensis community is relatively unstable (36.84/63.16). The ecology is somewhat fragile, indicating that the community is still in the early or middle stage of competing with other species for resource utilization. For species protection and ecological recovery, choose species with strong positive associations for succession. The community structure and function are a protection to establish a suitable environment for Hopea hainanensis and finally achieve the purpose of adequate protection.